Membangun Percaya Diri Remaja Kristen melalui Mentoring Di Era Digital - Pekerti Mendrofa, Windy; Santosa; Tabrani, Ahmad (Tumou Tou, 2024)
Self-confidence plays a significant role and has influence in the lives of  Christian teenagers in the digital era. Teenage confidence can be developed through non-formal Christian education. Mentoring is a strategy applied in non-formal Christian education. This research aims to describe the influence of mentoring implementation on the confidence of teenage participants in the non-formal Christian education program "Future Center" by the PESAT Foundation Cluster in West Kalimantan. The study involved  61 teenagers who received mentoring services. This research used a quantitative method. The results of the study are as follows: mentoring implementation has an influence on teenage confidence, with a correlation of 0.462 in the category of moderate or significant positive correlation. The mentoring process influences teenage confidence by 21.4%, with the remaining 78.6% influenced by other factors outside the mentoring process. The regression coefficient is 0.444, indicating that each addition of one point or treatment to the mentoring process will result in a 0.444-fold increase in confidence. Conversely, if the implementation of mentoring is abolished or weakened, it will weaken the confidence of adolescents. The implementation of mentoring influences teenage confidence; therefore, it is important for mentors to develop quality in mentoring implementation.